2020
DOI: 10.1186/s12936-020-03307-4
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of artemether-lumefantrine in the treatment of uncomplicated Plasmodium falciparum malaria in Chewaka District, Ethiopia

Abstract: Background The efficacy of artemether-lumefantrine (AL) for treatment of uncomplicated Plasmodium falciparum malaria in south-western Ethiopia is poorly documented. Regular monitoring of drug efficacy is an important tool for supporting national treatment policies and practice. This study investigated the therapeutic efficacy of AL for the treatment of P. falciparum malaria in Ethiopia. Methods The study was a one-ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…An adverse event was de ned as any undesirable medical occurrence (symptoms, signs or laboratory ndings) in a patient once they were enrolled to the studies regardless of whether it was related to the treatment. Adverse events were judged according to their causal association with AL (unlikely, possible and probable) and severity (mild, moderate or severe) [7].In this review, mild adverse events (a headache, cough, fever, diarrhoea, vomiting, perioral ulcer, anorexia, abdominal pain, dizziness and nausea, weakness/fatigue and others) were reported and almost all were resolved soon after completion of the treatment except cough [48,53,54]. Similar mild adverse events have been associated with AL, the most common being headache, fever, vomiting followed by gastrointestinal disturbances [65,69].The observed rate of 36.1%, (550/1523)ADRs was comparable with the rate reported in the previous review in Ethiopia where 269 of 633 patients had ADRs, with a pooled event rate of 41.2% [68].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…An adverse event was de ned as any undesirable medical occurrence (symptoms, signs or laboratory ndings) in a patient once they were enrolled to the studies regardless of whether it was related to the treatment. Adverse events were judged according to their causal association with AL (unlikely, possible and probable) and severity (mild, moderate or severe) [7].In this review, mild adverse events (a headache, cough, fever, diarrhoea, vomiting, perioral ulcer, anorexia, abdominal pain, dizziness and nausea, weakness/fatigue and others) were reported and almost all were resolved soon after completion of the treatment except cough [48,53,54]. Similar mild adverse events have been associated with AL, the most common being headache, fever, vomiting followed by gastrointestinal disturbances [65,69].The observed rate of 36.1%, (550/1523)ADRs was comparable with the rate reported in the previous review in Ethiopia where 269 of 633 patients had ADRs, with a pooled event rate of 41.2% [68].…”
Section: Discussionmentioning
confidence: 99%
“…The summary characteristics of the included studies are shown in Table 1.Fifteen studies satis ed the inclusion criteria and were included in this systematic review and meta-analysis with a total sample size of 1523 participants that ranged from 60 patients [46] to 315 patients [47]. Seven of the studies were interventional [47,48,49,50,51,52,53], and the other eight studies were observational study [46,54,55,56,57,58,59,60].These studies were conducted in different malarious parts of the Country with varied transmission intensity (Fig. 2).…”
Section: Baseline Characteristics Of Studies Conducted To Test the E mentioning
confidence: 99%
See 3 more Smart Citations